Are Voluntary Agreements Better? Evidence from Baseball Arbitration - John W. Budd; Aaron J. Sojourner; Jaewoo Jung (Institute for the Study of Labor (IZA), 2014)
This paper empirically examines the widespread belief that voluntarily negotiated agreements produce better long-run relationships than third-party imposed settlements, such as arbitrator decisions or court judgments. Two key outcomes are analyzed – subsequent player performance and the durability of club-player relationship. Major League Baseball provides a compelling setting for these analyses because individual performance is well measured, there is the possibility of relationship breakdown, and both voluntary and imposed settlements are routinely used. While the results clearly show that a third-party imposed settlement is not better than a voluntary one, the evidence in support of the widespread belief is mixed.
Keywords: J52; M12; M5; 330; dispute resolution; arbitration; negotiation; salary; sports; baseball